2020
DOI: 10.11152/mu-2332
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound is useful in oncohematologic patients with respiratory dysfunction admitted to an Intensive Care Unit (ICU): a pilot study

Abstract: Aims: This pilot study aimed to evaluate the usefulness of a sequential lung ultrasound score (LUS) in immunosuppressed patients with oncohematologic diseases and acute respiratory dysfunction hospitalized in an intensive care unit (ICU).Materials and methods: LUS was calculated at ICU admission, after 24 h, 48 h and at discharge. A score ranging from 0 to 26 was attributed according to the number of B lines, presence of lung consolidation and pleural effusion.Results: Twenty-six patients were included. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Many authors have proven the accuracy of TUS, and its high sensitivity ranges from 57% to 100%, and specificity ranges from 54% to 99% for diagnosing pneumonia in the general population. [ 11 , 20 ] Although few studies have evaluated TUS in hematologic patients, Gomez-Ravetti et al [ 21 ] described the use of sequential TUS in immunosuppressed patients with hematologic disease and acute respiratory dysfunction. They concluded that TUS might be a helpful tool for predicting the severity at admission, however, they did not compare its results with those of CT. More recently, TUS may play a role in detecting changes before symptom onset in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have proven the accuracy of TUS, and its high sensitivity ranges from 57% to 100%, and specificity ranges from 54% to 99% for diagnosing pneumonia in the general population. [ 11 , 20 ] Although few studies have evaluated TUS in hematologic patients, Gomez-Ravetti et al [ 21 ] described the use of sequential TUS in immunosuppressed patients with hematologic disease and acute respiratory dysfunction. They concluded that TUS might be a helpful tool for predicting the severity at admission, however, they did not compare its results with those of CT. More recently, TUS may play a role in detecting changes before symptom onset in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have proven the accuracy of TUS, and its high sensitivity ranges from 57% to 100%, and speci city from 54% to 99% for diagnosing pneumonia in general population [10,16]. Although few studies have evaluated TUS in hematologic patients, Gomez-Ravetti et al [17] described the use of sequential TUS in immunosuppressed patients with hematologic disease and acute respiratory dysfunction. They concluded that TUS might be a helpful tool for predicting the severity at admission, however, they did not compare its results with CT. More recently, TUS has been proven to have an early diagnosis, even before the onset of clinical respiratory symptoms in pediatric patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound exams were performed in three-time points with 3 to 4 seconds image acquisition (recorded) in each area: inclusion in the study, after 48 hours, and on the seventh day after inclusion. The images were acquired by a same physician experienced in intensive care and in performing point of care ultrasound examinations at the bedside ( Gómez Ravetti, et al 2020 ). US protocol was adapted from Soummer et al ., and included four areas in each hemithorax: anterior (2 o intercostal space –ICS- at a midclavicular line), lateral (anterior axillary line at 5 o ICS), posterior region (posterolateral alveolar and/or pleural syndrome - PLAPS), and costophrenic region ( Soummer, et al 2012 ) ( Figure 1 )
Figure 1 Thorax ultrasound protocol regions scanned.
…”
Section: Methodsmentioning
confidence: 99%